Perlindungan Hukum Hak Cipta terhadap Pengunggahan film Bioskop Yang Diunggah Ke Instastory Tanpa Izin Hak Pencipta - Utami, Dayang Sasa Sismia; Raodah, Putri (Bagian Hukum Bisnis Fakultas Hukum Universitas Mataram, 2024)
This study aims to determine the legal protection given to cinema film copyright holders against uploading films through instastories without permission and to find out what efforts copyright holders can take regarding the uploading of cinema films without permission. The research method used is normative legal research method by using the method of statutory approach and conceptual approach. The results of this study indicate that preventive legal protection is carried out by fulfilling the rights of creators and copyright holders. Repressive legal protection in the Copyright Protection Act can be in the form of administrative sanctions, imprisonment and fines and additional criminal sanctions because the perpetrator commits the prohibition. Copyright legal protection is contained in the Copyright Law no. 28 of 2014, Law no. 11 of 2008 concerning ITE, and Law no. 33 of 2009 concerning Film. Then the efforts made by copyright holders regarding uploading without permission in the Copyright. The government protects copyrights and related rights in the world of information and communication technology (ICT). The government and judicial bodies carry out law enforcement. Copyright law enforcement is carried out by the government involving ministries. The legal remedies that copyright holders can take regarding uploading without permission have been regulated in the Copyright Act. Creators or copyright holders can take legal steps to obtain legal protection in the field of copyright, there are several legal steps that copyrights holders, including Mediation, criminal complaints, compensation lawsuits, content closure reports and Access Rights can take.